Morphology and optical constants of nanographite films created by thermal vacuum deposition - Kozachenko, V.V.; Kondratenko, O.S.; Normand, F.Le (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
The method for nanographite films preparation using thermal sublimation in vacuum of graphite nanoparticles under ultrasound treatment was proposed. Studied in the system nanographite film – substrate were composition and morphology of a multilayer interface system by using ellipsometry and Raman scattering. It has been ascertained that the optical parameters of discontinuous nanographite films strongly depend on morphology of the surface layer. Using the results of ellipsometric measurements, we determined the effective optical onstants, thickness of the films and calculated the volume composition of the solid phase in the film within the framework of the model of effective environment by Bruggeman